The Effect of Cytokines and CD Markers in Patients Infected with COVID- 19 - Ali Anok Njum, Jabbar Afate ALwane2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Study aimed to show the effect of inflammatory mediators ( IL-6 and gamma interferon) and moleculesCD54 & CD2 in patients infected with COVID-19A overall of (100) positive patients for COVID-19 were selected for project .Patients attended general lab.With sings of COVID-19 then select to expression 0f gamma interferon & IL-6 in serum of patient andindication expression of CD54 and CD2in serum of patients. Results indicated that gamma interferon &IL-6 highly important increases (p<0.001) in serum level of covid- 19 patients as matched with healthycontrol groups , acute covid 19 exposed great as well as , rises in serum near of gamma interferon &IL-6 pointedly(p<0.001) ,although modest cases of disease show great proliferation in serum level of IL-6expressively(p<0.001).immune molecules showed more expression of CD2 & CD54 in covid- 19 patientsas matched with healthy normal groups.